A comprehensive finite element model of surgical treatment for cervical myelopathy. (April 2020) - Stoner, Kirsten E.; Abode-Iyamah, Kingsley O.; Fredericks, Douglas C.; Viljoen, Stephanus; Howard, Matthew A.; Grosland, Nicole M.
Abstract: Background: Cervical myelopathy is a common and debilitating chronic spinal cord dysfunction. Treatment includes anterior and/or posterior surgical intervention to decompress the spinal cord and stabilize the spine, but no consensus has been made as to the preferable surgical intervention. The objective of this study was to develop an finite element model of the healthy and myelopathic C2-T1 cervical spine and common anterior and posterior decompression techniques to determine how spinal cord stress and strain is altered in healthy and diseased states. Methods: A finite element model of the C2-T1 cervical spine, spinal cord, pia, dura, cerebral spinal fluid, and neural ligaments was developed and validated against in vivo human displacement data. To model cervical myelopathy, disc herniation and osteophytes were created at the C4-C6 levels. Three common surgical interventions were then incorporated at these levels. Findings: The finite element model accurately predicted healthy and myelopathic spinal cord displacement compared to motions observed in vivo . Spinal cord strain increased during extension in the cervical myelopathy finite element model. All surgical techniques affected spinal cord stress and strain. Specifically, adjacent levels had increased stress and strain, especially in the anterior cervical discectomy and fusion case. Interpretations: This model is the first biomechanically validated, finite element model of the healthy and myelopathic C2-T1 cervical spine and spinal cord which predicts spinal cord displacement, stress, and strain during physiologic motion. Our findings show surgical intervention can cause increased strain in the adjacent levels of the spinal cord which is particularly worse following anterior cervical discectomy and fusion. Highlights: We made a finite element model of healthy and myelopathic cervical spine and cord. The finite element model was validated using in vivo human spinal cord motion data. We modeled surgical techniques to see how spinal cord stress and strain changed. Surgical intervention increased strain in the adjacent levels of the spinal cord.